The Improve Algorithm of the Sky Illumination Rendering - Wenlong Yu; Limin Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper proposed the algorithm of the sky color rendering based on the relationship between the height of viewpoint and the altitude of scattering point with atmospheric density after the study of atmospheric absorption and scattering and sky illumination simulation methods. It proposed the simplified algorithm of the sky perspective illumination. The geometrical model of the sky dome and rotation and the sun location is presented. The rendering method based on GPU is designed. The results of experiment show that the rendering effect of the sky illumination based on this algorithm is realism. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2000